THEORETICAL FOUNDATIONS OF THE FORMATION OF PROFESSIONAL COMPETENCIES OF FUTURE TEACHERS (Web of Teachers: Inderscience Research, 2024)
The formation of professional competencies among future teachers is a critical aspect of modern pedagogical education. This article explores the theoretical foundations underlying the development of these competencies, emphasizing the integration of knowledge, skills, and values necessary for effective teaching. The study examines key frameworks for competency-based education, highlighting the role of reflective practice, experiential learning, and interdisciplinary approaches in preparing teachers for dynamic educational environments. Additionally, the article discusses the influence of modern technologies and innovative teaching methods in fostering professional growth. By addressing these theoretical aspects, the study provides a comprehensive foundation for developing effective strategies to enhance teacher training programs and ensure the readiness of future educators for professional challenges.